Association of Neighborhood Opportunity, Race, and Ethnicity with Pediatric Day-of-surgery Cancellations: A Cohort Study - Willer, Brittany L; Mpody, Christian; Tobias, Joseph D; Nafiu, Olubukola O; Jimenez, Nathalia (Anesthesiology (Philadelphia), 2024)
Day-of-surgery cancellations impede healthcare access and contribute to inequities in pediatric healthcare. Socially disadvantaged families have many risk factors for surgical cancellation, including low health literacy, transportation barriers, and childcare constraints. These social determinants of health are captured by the Child Opportunity Index 2.0, a national quantification of neighborhood-level characteristics that contribute to a child's vulnerability to adversity. This study examined the association of neighborhood opportunity with pediatric day-of-surgery cancellations. A retrospective cohort study of children younger than 18 yr of age scheduled for ambulatory surgery at a tertiary pediatric hospital between 2017 and 2022 was conducted. Primary addresses were geocoded to determine Child Opportunity Index 2.0 neighborhood opportunity. Log-binomial regression was used to estimate the relative risk of day-of-surgery cancellation comparing different levels of neighborhood opportunity. This study also estimated the relative risk of cancellations associated with race and ethnicity, by neighborhood opportunity. Overall, the incidence of day-of-surgery cancellation was 3.8%. The incidence of cancellation was lowest in children residing in very-high-opportunity neighborhoods and highest in children residing in very-low-opportunity neighborhoods (2.4% vs. 5.7%, P < 0.001). The adjusted relative risk of day-of-surgery cancellation in very-low-opportunity neighborhoods compared to very-high-opportunity neighborhoods was 2.24 (95% CI, 2.05 to 2.44; P < 0.001). The results showed statistical evidence of an interaction of Children's Opportunity Index with race and ethnicity. In very-low-opportunity neighborhoods, Black children had 1.48 times greater risk of day-of-surgery cancellation than White children (95% CI, 1.35 to 1.63; P < 0.001). Likewise, in very-high-opportunity neighborhoods, Black children had 2.17 times greater risk of cancellation (95% CI, 1.75 to 2.69; P < 0.001). This study found a strong relationship between pediatric day-of-surgery cancellation and neighborhood opportunity. Black children at every level of opportunity had the highest risk of cancellation, suggesting that there are additional factors that render them more vulnerable to neighborhood disadvantage.